Media Dan Motivasi Belajar; Kritik Eksplanasi Konstruktif Dalam Implementasi Strategi Pembelajaran - Abdul Hamid Wahid; Chusnul Muali; Dhuyufallah Dhuyufallah (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2018)
Motivation learners today are experiencing a lot of fluctuating. This makes the learners in following the learning process seem only fulfill the obligation to take the exam. Therefore, teachers as facilitators who have full responsibility in educating and educating children of the nation are required to have a strategy that can change the learning paradigm of learners to be able to improve learning motivation. Teachers need to apply learning innovations that can foster motivation and develop the creativity of learners. The selection of strategies as an appropriate learning innovation certainly provides a broad impact on the results and learning achievements of learners. In addition, efforts made by teachers in improving motivation learners can not be separated from the selection of methods and the right learning approach as well. Appropriate learning methods and approaches are intended to accommodate the interests of fulfillment and achievement of predetermined learning objectives. In every implementation of learning methods and approaches, learning and media resources are needed to help learners understand and apply the learning materials developed by the teacher.